2010
DOI: 10.1111/j.1365-2621.2010.02187.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of pearl millet flour with soybean protein: effect of cooking on in vitro protein digestibility and essential amino acids composition

Abstract: In vitro protein digestibility (IVPD) and amino acids profile of pearl millet (Dempy cultivar) supplemented with soybean protein (5-15%) were investigated. Supplementation of dempy flour with soybean protein steadily decreased IVPD with increasing the portion of soybean in the blend. The in vitro protein digestibilities of the cooked supplemented dempy flours were higher when compared with the raw ones, whereas the highest value was that of the 5% soybean protein. All essential amino acids of dempy flour were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…While agronomic efficiency of nitrogen (AE N ) can be estimated through calculating the difference between grain yield with N and without N application divided by quantity of N applied (kg ha -1 ). The results of field experiments indicated that more than 50% of nitrogen is not assimilated in rice, wheat (Cassman et al 2002) and pearl millet (Ali et al 2010) particularly in unfavorable weather conditions. The recovery efficiency of N is persisted lower ((31±18)% in rice, (18±11)% in wheat and (30±12)% in pearl millet) than global cereal N use efficiency (33%).…”
Section: Improving Resource Use Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…While agronomic efficiency of nitrogen (AE N ) can be estimated through calculating the difference between grain yield with N and without N application divided by quantity of N applied (kg ha -1 ). The results of field experiments indicated that more than 50% of nitrogen is not assimilated in rice, wheat (Cassman et al 2002) and pearl millet (Ali et al 2010) particularly in unfavorable weather conditions. The recovery efficiency of N is persisted lower ((31±18)% in rice, (18±11)% in wheat and (30±12)% in pearl millet) than global cereal N use efficiency (33%).…”
Section: Improving Resource Use Efficiencymentioning
confidence: 99%
“…Nitrogen use efficiency (NUE) NUE can be described as aggregate efficiency index of contributions to crops derived from nitrogen uptake, N uptake efficiency and the plant N acquisition efficiency to convert in grain yield. It can be determined by dividing grain yield of a crop by N applied (Sowers et al 1994;Ali et al 2010). While agronomic efficiency of nitrogen (AE N ) can be estimated through calculating the difference between grain yield with N and without N application divided by quantity of N applied (kg ha -1 ).…”
Section: Improving Resource Use Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementation significantly increased lysine 1.5‐ to 2.4‐fold. In addition, essential amino acid content remained higher in the cooked composite flours when compared with the cooked native millet flour (Ali and others ). It has also been found that supplementation of pearl millet with whey protein resulted in a significant increase in protein content compared to the control.…”
Section: Food Manufacturing and Formulation Technologiesmentioning
confidence: 99%
“…Group 4 recorded the highest Net Protein Utilization (NPU) followed by group 3 and group 2, respectively. The higher the BV, TD, and NPU the better the protein quality, the standard for protein quality measurement ranged from 70 to 90% (Ali, El Tinay, Mallasy & Yagoub, 2010). The result obtained for protein quality of animals fed with experimental diets indicated that the protein content present in the experimental cookies was well utilized and appeared to be significant in animal growth and development.…”
Section: Nutritional Evaluation Of Cookiesmentioning
confidence: 99%